Andalusian nature and its impact on Color investment (Journal of the College of Basic Education, 2023)
It was self-evident that the Andalusian nature, and we showed it the most fertile and green of God’s places -According to what the sources conveyed to us - a major topic in the Andalusian poem, and it was obvious that it would beDescription The poets' means of conveying its splendid scenes and its enchanting beauties in its flowers and roses.its trees, fruits, water, gardens and orchards, and he was able to describe what poets mocked himThe most important of which was the color to be the best witness and the best carrier of the Andalusian nature in general.The temptress is the push in